Inhibition of Struvite Crystal Growth with The Addition of Carboxylic Acid Using Batch Operation - Dyah Suci Perwitasari; Sintha Soraya Santi; Muhammad Aji Pangestu; Yahya A. (Nusantara Science and Technology Proceedings, 2021)
Tartaric acid and maleic acid are carboxylic acids that effectively inhibit the growth of struvite crystals and weak organic acids that are friendly environments. The purpose of this study was to determine the effectiveness of inhibition of struvite crystal growth from the effect of adding carboxylic acid (tartaric acid and maleic acid) using batch operation which can be used as a slow-release fertilizer. Struvite is an effective phosphate fertilizer as an alternative source of rock phosphate to maintain agricultural production systems. From the results of the study, tartaric acid was found to be 10,483 mg at a temperature of 40oC with a concentration of 20 ppm and stirrer rotation of 300 rpm which was a better optimum condition to be applied in the struvite fertilizer industry when compared to maleic acid. Characterization of struvite crystals using XRPD Rietveld and SEM-EDX methods.